Wheat price hikes and food security in Sub-Saharan Africa - Laborde Debucquet, David; Piñeiro, Valeria (Springer, 2023)
The Russia–Ukraine conflict affected the price of staple crops and spurred interest in tropical wheat production. Regional consumption patterns and trade are better placed to guide effective and sustainable food security policy strategies.